Forensic economic examination in the investigation of corruption crimes (Law and Safety, 2022)
In the investigation of corruption offenses, the most effective procedural form of using special knowledge is a forensic economic examination. However, the procedure for conducting forensic economic expertise in Ukraine is not without drawbacks, and when carried out within the framework of the investigation of specific corruption crimes is characterized by certain features. The purpose of the article is to generalize and systematize key features, as well as to identify weaknesses in the process of forensic economic examination in the investigation of corruption crimes in Ukraine.In order to achieve the goal, the legislative interpretation of the concept of “corruption crime” has been investigated. On the basis of statistical information, indicators have been calculated and the dynamics and structure of recorded corruption criminal offenses in Ukraine in 2018–2022 have been analyzed. On the basis of analysis, systematization and generalization of normative and scientific sources the essence, process of emergence and development of the concept of forensic economic expertise has been investigated. The role and importance of forensic economic expertise in the investigation of corruption crimes has been substantiated. The list of basic documents, thorough examination of which by a forensic expert is the basis for detecting corruption, has been systematized. The features of forensic economic examination in the investigation of specific corruption offenses defined by the current legislation of Ukraine have been investigated. The procedure for appointing and conducting forensic economic expertise in Ukraine has been analyzed and its shortcomings and weaknesses have been identified.Prospects for further research in this area are the study of foreign experience in conducting forensic economic examination in the investigation of corruption crimes, the development of practical recommendations for eliminating the identified shortcomings and improving the procedure for appointing and conducting forensic economic examinations in Ukraine. Purposeful, though gradual, movement in the direction of solving the problem of corruption in Ukraine is a guarantee of strengthening all spheres of public life.
Keywords: corruption; corruption crimes; special economic knowledge; forensic economic examination; forensic accounting examination.